Reciprocal Teaching assisted by GeoGebra to Improve Students Mathematical Communication - Moh. Rikza Muqtada; Santi Irawati; Abdul Qohar (Pascasarjana Universitas Negeri Malang (UM), 2018)
Abstract: This Classroom Action Research (CAR) aims to describe the implementation of the reciprocal teaching learning model assisted by Geogebra to improve the mathematical communication skills of the 11th graders of Vocational students. The researcher conducted this research in two cycles. The results of this study indicate that there is an increase in students’ mathematical communication skills from cycle I to cycle II. Reciprocal teaching consists of four stages: summarizing, questioning, predicting and clarifying.Key Words: reciprocal teaching, GeoGebra, mathematical communicationAbstrak: Penelitian Tindakan Kelas (PTK) ini bertujuan untuk mendeskripsikan implementasi model pembelajaran reciprocal teaching berbantuan Geogebra yang dapat meningkatkan kemampuan komunikasi matematis peserta didik kelas XI SMK. Peneliti melakukan penelitan ini dalam dua siklus. Hasil penelitian ini menunjukkan bahwa kemampuan komunikasi matematis peserta didik meningkat dari siklus I ke siklus II. Reciprocal teaching terdiri dari empat tahap yaitu merangkum (summarizing), menanya (questioning), memprediksi (predicting), dan mengklarifikasi (clarifying).Kata kunci: reciprocal teaching, GeoGebra, komunikasi matematis